2020
DOI: 10.1101/2020.09.28.20203299
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictive Modelling of COVID-19 New Cases in Algeria using An Extreme Learning Machines (ELM)

Abstract: In this research, an extreme learning machine (ELM) is proposed to predict the new COVID-19 cases in Algeria. In the present study, public health database from the Algeria health ministry has been used to train and test the ELM models. The input parameters for the predictive models include Cumulative Confirmed COVID-19 Cases (CCCC), Calculated COVID-19 New Cases (CCNC), and Index Day (ID). The predictive accuracy of the seven models has been assessed via several statistical parameters. The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Djeddou et al [17] predicted new COVID-19 cases in Algeria. The utilized dataset was obtained from the public health database of the Algeria health ministry.…”
Section: Studies Examining African Casesmentioning
confidence: 99%
“…Djeddou et al [17] predicted new COVID-19 cases in Algeria. The utilized dataset was obtained from the public health database of the Algeria health ministry.…”
Section: Studies Examining African Casesmentioning
confidence: 99%
“…An extreme learning machine (ELM) was used to predict the COVID-19 new cases in Algeria. The results showed that the proposed ELM model achieved an adequate level of prediction accuracy with smallest errors [14].…”
Section: Introductionmentioning
confidence: 99%
“…An extreme learning machine (ELM) was used to predict the COVID-19 new cases in Algeria. The results showed that the proposed ELM model achieved an adequate level of prediction accuracy with smallest errors [14]. In this study, four artificial neural network models namely (radial basis function neural networks "RBFNN", generalized regression neural networks (GRNN), Extreme learning machine (ELM), and multi-layer perceptron neural network (MLPNN) are proposed for predictive modeling of COVIS-19 new confirmed cases (CNCC) in Algeria.…”
Section: Introductionmentioning
confidence: 99%